Cloning of the cDNA and partial sequencing of the gene that codifies the sheep hepatic enzyme glutamate dehydrogenase - Mello, Sandra Regina de; Tavares, Kaio César Simiano; Rosa, Carlos André da Veiga Lima; Miletti, Luiz Claudio (Revista de Ciências Agroveterinárias, 2013)
The mitochondrial enzyme Glutamate Dehydrogenase (GDH: EC 1.4.1.2) catalyzes the reversible deamination of the L-glutamate for 2-oxoglutarate (α-ketoglutarate) using NAD+ and NADP+ as coenzymes. It is one of the most important liver enzymes found in hepatocytes of cattle, sheep and goats. Infections by Fasciola spp., severe acute intoxication by toxins of plants such as Xanthium spp. and Senecio spp. as well as intoxication by copper result in the release of this enzyme in blood. The increase of the GDH indicates damage or hepatic necrosis in cattle and sheep. This is an enzyme of choice to evaluate the function of the ruminants. In the present study the cDNA, that codifies the GDH enzyme of the hepatocyte of sheep, was synthesized by means of RT-PCR making use of mRNA extracted from the liver of sheep. Part of the region where the cDNA of the GDH of the ovine is codified was amplified by PCR from primers synthesized through the comparison of the aligned sequences of Ovis aries, Bos taurus, Homo sapiens, Rattus norvegicus and Mus musculus available in the database. The cDNA was cloned in the vector pGEM®-T Easy (Promega) and inserted in Escherichia coli DH10B calcium competent cells by heat shock procedure. The plasmid DNA was purifi ed and after sequencing, the presence of 1292 pb was confirmed. The alignment of the sequence deduced of amino acid with other species revealed high homology among the GDHs.